Moving toward a universally accessible web: Web accessibility and education. Issue 4 (8th August 2019) - Kurt, Serhat
ABSTRACT: The World Wide Web is an extremely powerful source of information, inspiration, ideas, and opportunities. As such, it has become an integral part of daily life for a great majority of people. Yet, for a significant number of others, the internet offers only limited value due to the existence of barriers which make accessing the Web difficult, if not impossible. This article illustrates some of the reasons that achieving equality of access to the online world of education is so critical, explores the current status of Web accessibility, discusses evaluative tools and methods that can help identify accessibility issues in educational websites, and provides practical recommendations and guidelines for resolving some of the obstacles that currently hinder the achievability of the goal of universal Web access.